KAJIAN ALAT TANGKAP RAMAH LINGKUNGAN DI KABUPATEN KAIMANA PROVINSI PAPUA BARAT - Malfino Dimara; Fanny FC Simatauw; Handayani Handayani; Selvi Tebaiy; Fitriyah I.E Saleh (Journal of Tropical Diversity, 2025)
There are many types of bagan fishing gear, gill nets, hand lines, trolling lines, long lines, and bubu fishing gear operated by fishermen in Kaimana. Fishing gear and fishing aids that are poorly controlled, not selective and damage the waters are estimated to trigger excessive fishing and can threaten the lives of marine biota and the sustainability of fish stocks. This study aims to determine the study of environmentally friendly fishing gear in Kaimana Regency and to determine the fish catch based on the fishing gear operated. The study was conducted in 4 villages in Kaimana Regency, namely Air Merah Village, Coa Village, Arguni Village, and Buruway Village in June - August 2024. The method used in the study was a descriptive method with an interview technique with 33 respondents. The results of the interview showed that there were 6 types of fishing gear used by the community, namely, millennium gill nets, floating nets (bagan), Hand Lines, Long Lines, Tonda Lines, and Bubu (Traps). The assessment results of the CCRF (Code of Conduct for Responsible Fisheries) obtained six types of fishing gear, namely, millennium gill nets with a score of 28.3, floating nets 29.5, hand lines 32.9, longlines 29.8, trolling lines 32.2, and bubu obtained a score of 34.7. These results indicate that the fishing gear operated in Kaimana Regency is very environmentally friendly because it meets the very good CCRF criteria.